APPLICATION OF ENVIRONMENTAL, SOCIAL AND GOVERNANCE PRINCIPLES INTEGRATED: THE CASE OF PT. SOLUSI BANGUN INDONESIA TBK. IN REACHING GOLD PROPER IN 2022 - Lianto, Miguel (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
This research uses data. Secondary data from the 2018-2022 sustainability report was used with purposive sampling. Data analysis uses the content analysis method. Stakeholders determine materiality by focusing on customers, shareholders, employees, government, work partners, suppliers and mass media. Environmental aspects are considered the main material issue. Highest disclosure of carbon emissions in the Energy Consumption Category or EC sub-sector 2. Corporate governance supports community empowerment programs with an SROI of 8.70 (based on the author's calculations), which results in a Gold PROPER award. Overall, the assessment of materiality, quality of disclosure, governance company, and return on social investment at PT. Solusi Bangun Indonesia Tbk is considered good. Recommendations are provided so that companies can maintain and improve ESG implementation.